Skazany na peryferie? Poznański Tarpan na tle sytuacji wzornictwa przemysłowego epoki gierkowskiej - Szatan, Katarzyna (Człowiek i Społeczeństwo, 2017)
Katarzyna Szatan, Skazany na peryferie? Poznański Tarpan na tle sytuacji wzornictwa przemysłowego epoki gierkowskiej [Condemned to the periphery? The Poznan Tarpan in the context of the industrial design situation of the Gierek era], edited by W. Bryl-Roman, „Człowiek i Społeczeństwo” vol. XLIII: Projektowanie w latach 70. [Designing in the 1970s], Poznań 2017, pp. 89-114, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. The paper recalls the history of Tarpan – one of the undervalued achievements of the Polish industrial design of the 1970’s. The case of this delivery van, designed for agricultural purposes, proves that Polish designing of that time was not in as poor condition as it is repeatedly portrayed to be. Seen in the context of present industrial design theory redefinitions, it reveals unilateralism and superficiality of the evaluations made by the native design historians. Adopting a dual approach – without neglecting the historical context, nor the contemporary reassessments – is an opportunity to review the Polish design of the 1970’s and possibly to make a modest contribution to the reinterpretation of the whole People’s Poland period.